PERANCANGAN SISTEM ANGKAT FORKLIFT DENGAN KAPASITAS ANGKAT 7 TON - Jimmy Jimmy; Frans Jusuf Daywin; G Soeharsono (Jurnal Ilmiah Teknik Mesin POROS, 2017)
Abstract: Forklift is one of the lifting machines that use to lift and move loads which can move loads with a diffirent height without taking a long time than we lift it by people’s strength. The Applications of forklift can be seen at sea port area and loading area in industrial. The design of forklift must be applied to find the hydraulic system and the strenght for the forklift so it will definitely lift the cargo which want to be lifted. Design of forklift consists of design hydraulic system and strength for the forklift.. The design of forklift with 7 tons of capacity will be disscused in this thesis.